(untitled) (Swiss Medical Weekly, 2014)
BACKGROUND: Neuroendocrine neoplasms (NENs) are difficult to diagnose. We used SwissNET data to characterise NEN patients followed in the two academic centres of western Switzerland (WS), and to compare them with patients followed in eastern Switzerland (ES) as well as with international guidelines. METHOD: SwissNET is a prospective database covering data from 522 consecutive patients (285 men, 237 women) from WS (n = 99) and ES (n = 423). RESULTS: Mean ± SD age at diagnosis was 59.0 ± 15.7 years. Overall, 76/522 experienced a functional syndrome, with a median interval of 1.0 (IQR: 1.0–3.0) year between symptoms onset and diagnosis. A total of 51/522 of these tumours were incidental. The primary tumour site was the small intestine (29%), pancreas (21%), appendix (18%) and lung (11%) in both regions combined. In all, 513 functional imaging studies were obtained (139 in WS, 374 in ES). Of these, 381 were 111In-pentetreotide scintigraphies and 20 were 68Ga-DOTATOC PET. First line therapy was surgery in 87% of patients, medical therapy (biotherapy or chemotherapy) in 9% and irradiation in 3% for both regions together. CONCLUSION: Swiss NEN patients appear similar to what has been described in the literature. Imaging by somatostatin receptor scintigraphy (SRS) is widely used in both regions of Switzerland. In good accordance with published guidelines, data on first line therapy demonstrate the crucial role of surgery. The low incidence of biotherapy suggests that long-acting somatostatin analogues are not yet widely used for their anti-proliferative effects. The SwissNET initiative should help improve compliance with ENETS guidelines in the workup and care of NEN patients.